Sunnah dalam Nalar Islam Kontemporer Nasr Hamid Abu Zayd - Mahmudah, Nur (Program Pascasarjana UIN Sunan Ampel Surabaya, 2012)
This paper deals with the notion of Sunna according to one of the most leading contemporary Muslim thinkers, Nasr Hamid Abu Zayd. The paper explores both his view concerning the Sunna, and his methodology of how to understand it. The paper discovers that the man does find in the Sunna a kind of flexibility that makes it open for new understanding and application within new context. His conception of the Sunna can be found in his ideas concerning the nature, position, validity and the interpretation of religious text. Given that the Sunna comes only second after the Qurâan, the former must therefore be interpreted in the light of the latter. The paper tries to show that what is interesting about studying Abu Zayd is his view to transform the Islamic religious texts from merely mythological narratives into a logical and living tradition.